Cardiac myxomas: clinical presentation, diagnosis and management - Griborio-Guzman, Andres G; Aseyev, Olexiy I; Shah, Hyder; Sadreddini, Masoud (Heart (British Cardiac Society), 2022)
Cardiac myxomas (CM) are the most common type of primary cardiac tumours in adults, which have an approximate incidence of up to 0.2% in some autopsy series. The purpose of this review is to summarise the literature on CM, including clinical presentation, differential diagnosis, work-up including imaging modalities and histopathology, management, and prognosis. CM are benign neoplasms developed from multipotent mesenchyme and usually present as an undifferentiated atrial mass. They are typically pedunculated and attached at the fossa ovalis, on the left side of the atrial septum. Potentially life-threatening, the presence of CM calls for prompt diagnosis and surgical resection. Infrequently asymptomatic, patients with CM exhibit various manifestations, ranging from influenza-like symptoms, heart failure and stroke, to sudden death. Although non-specific, a classic triad for CM involves constitutional, embolic, and obstructive or cardiac symptoms. CM may be purposefully characterised or incidentally diagnosed on an echocardiogram, CT scan or cardiac MRI, all of which can help to differentiate CM from other differentials. Echocardiogram is the first-line imaging technique; however, it is fallible, potentially resulting in uncommonly situated CM being overlooked. The diagnosis of CM can often be established based on clinical, imaging and histopathology features. Definitive diagnosis requires macroscopic and histopathological assessment, including positivity for endothelial cell markers such as CD31 and CD34. Their prognosis is excellent when treated with prompt surgical resection, with postsurgical survival rates analogous to overall survival in the age-matched general population.